Correlation between serum ferritin and glycaemic control in patients of type 2 diabetes mellitus: a case control study - Maheshwari, Amitkumar Virji; Bhoi, Bharat K.; Sadariya, Bhavesh R.; Javia, Hardik N.; Gusani, Jigar K.; Sharma, Hariom (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. Ferritin is a ubiquitous intracellular protein complex that reflectes the iron stores of the body. Many cross-sectional studies indicate that increased body iron stores have been associated with the development of glucose intolerance, type 2 diabetes, metabolic syndrome. This study was carried out to find out the relationship between serum ferritin and type 2 diabetes and to see the influence of body iron stores on HbA1c and blood glucose. Methods: This study includes 50 patients suffering from type 2 diabetes and compared with controls at Sir T hospital, Bhavnagar. S. ferritin, Fasting Blood Sugar (FBS), Post Prandial Blood Sugar (PPBS) and HbA1c were measured. Results: Serum ferritin was significantly higher (p<0.0001) in the patients suffering from type 2 diabetes and the correlation between serum ferritin and HbA1c was positive. Patients with type 2 diabetes with increased level of serum ferritin had poor glycemic control reflected by increased levels of HBA1c (r=0.701, p<0.0001) Conclusions: There is a positive association between elevated iron stores measured by serum ferritin levels and type 2 diabetes mellitus. Ferritin levels also correlated FBS, PP2BS and HbA1c.